A Low‐Current and Analog Memristor with Ru as Mobile Species. Issue 9 (27th January 2020) - Yoon, Jung Ho; Zhang, Jiaming; Lin, Peng; Upadhyay, Navnidhi; Yan, Peng; Liu, Yuzi; Xia, Qiangfei; Yang, J. Joshua
Abstract: The switching parameters and device performance of memristors are predominately determined by their mobile species and matrix materials. Devices with oxygen or oxygen vacancies as the mobile species usually exhibit a great retention but also need a relatively high switching current (e.g., >30 µA), while devices with Ag or Cu as cation mobile species do not require a high switching current but usually show a poor retention. Here, Ru is studied as a new type of mobile species for memristors to achieve low switching current, fast speed, good reliability, scalability, and analog switching property simultaneously. An electrochemical metallization‐like memristor with a stack of Pt/Ta2 O5 /Ru is developed. Migration of Ru ions is revealed by energy‐dispersive X‐ray spectroscopy mapping and in situ transmission electron microscopy within a sub‐10 nm active device area before and after switching. The results open up a new avenue to engineer memristors for desired properties. Abstract : Ruthenium is proposed and experimentally demonstrated to be able to serve as a new type of mobile species memristive devices with some desirable properties. An example device with a Pt/Ta2 O5 /Ru stack structure exhibits low switching current and voltage, fast speed, good scalability, and analog switching property simultaneously.